2017
DOI: 10.1371/journal.pone.0183317
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a movement-to-music video program on the objectively measured sedentary time and physical activity of preschool-aged children and their mothers: A randomized controlled trial

Abstract: Regular physical activity (PA) and the avoidance of prolonged sitting are essential for children’s healthy growth, and for the physical and mental wellbeing of both children and adults. In the context of exercise, music may promote behavioral change through increased exercise adherence and participation. The purpose of this study was to determine whether a movement-to-music video program could reduce sedentary behavior (SB) and increase PA in mother-child pairs in the home environment. A randomized controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…The current study is a subgroup analysis of an intervention group in randomized controlled trial (RCT) called Moving Sound [ 24 , 25 ], in where the main outcomes were children’s and their mothers’ sedentary time and PA during eight weeks’ period. The participants of the Moving Sound study were recruited between November 2014 and January 2016 from the cohort of NELLI: Pregnancy as a window to the future health of mothers and children, the 7-year follow-up of a gestational lifestyle intervention in the Pirkanmaa area, Finland (ISRCTN33885819; http://www.controlled-trials.com/ ).…”
Section: Methodsmentioning
confidence: 99%
“…The current study is a subgroup analysis of an intervention group in randomized controlled trial (RCT) called Moving Sound [ 24 , 25 ], in where the main outcomes were children’s and their mothers’ sedentary time and PA during eight weeks’ period. The participants of the Moving Sound study were recruited between November 2014 and January 2016 from the cohort of NELLI: Pregnancy as a window to the future health of mothers and children, the 7-year follow-up of a gestational lifestyle intervention in the Pirkanmaa area, Finland (ISRCTN33885819; http://www.controlled-trials.com/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Available literature of intervention studies concerning preschool children's physical activity revealed mixed findings. Some researchers posited that their respective interventions significantly increased children's physical activity [ 5 7 ], while others indicated no significant differences in physical activity emerged between intervention and control groups [ 8 10 ]. While these findings have shed light on offering practical implications to the physical activity interventions for this age group, most empirical studies to date have been implemented in the developed western countries, missing the important literature on this area of inquiry in the developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1596 articles were searched from each database, 1585 articles were excluded according to the inclusion and exclusion criteria. Finally, 11 articles were included in this study [31,[38][39][40][41][42][43][44][45][46][47]. (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Of them, 4 studies from Australia [38,40,45,46], 3 from the United States [31,42,44]. The United Kingdom [47], Germany [43], Finland [41], Norway and Sweden [39] each have one study. The included studies consisted of 10 RCTs [31,[38][39][40][41][43][44][45][46][47] and 1 CCT [42], with a total of 955 participants in the treatment group and 931 participants in the control group.…”
Section: Study Characteristicsmentioning
confidence: 99%